Advances in the treatment of pancreatic cancer with traditional Chinese medicine - Zhang, Yanhua; Xu, Hui; Li, Yue; Sun, Yang; Peng, Xiaochun (Frontiers in Pharmacology, 2023)
Pancreatic cancer is a common malignancy of the digestive system. With a high degree of malignancy and poor prognosis, it is called the "king of cancers”. Currently, Western medicine treats pancreatic cancer mainly by surgical resection, radiotherapy, and chemotherapy. However, the curative effect is not satisfactory. The application of Traditional Chinese Medicine (TCM) in the treatment of pancreatic cancer has many advantages and is becoming an important facet of comprehensive clinical treatment. In this paper, we review current therapeutic approaches for pancreatic cancer. We also review the protective effects shown by TCM in different models and discuss the potential molecular mechanisms of these.